PENGEMBANGAN LKPD BERBASIS MASALAH MATERI PECAHAN UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH KELAS V SD - Hazizah Br Barus, Siti; Sukmawarti; Hidayat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The objective of this research was to determine students' responses, validity, and effectiveness of problem-based LKPD on fractions material to improve problem-solving ability in fifth-grade elementary school students. It also aimed to determine the practicality of problem-based LKPD on fractions material to enhance problem-solving ability in fifth-grade elementary school students. The research design used was research and development (R&D). The subjects of this research were media experts, material experts, learning experts, and student responses. The object of this research was the student worksheet designed to assist teachers in the teaching and learning process. The developed LKPD was a problem-based LKPD on simple fractions material. This research resulted in a product in the form of a problem-based LKPD to improve problem-solving ability in fifth-grade elementary school students. The validity results of the feasibility assessment of LKPD from the overall expert evaluation obtained a percentage score of 96% from 20 statements. The validity results of the material expert assessment obtained an overall percentage of 91.11% from 9 statements. The practicality validation results of the LKPD were observed based on teacher and student response assessments, where the overall teacher response score reached 94% from 20 statements, and the overall student response score reached 92.5% from 10 statements. Based on the effectiveness aspect, the developed LKPD met the predetermined effectiveness criteria, with students' average scores before using the LKPD being 51.25% and increasing to 91.25% after using the LKPD.